Konseling sebagai Sanksi Pidana Tambahan pada Tindak Pidana Kekerasan dalam Rumah Tangga - Aroma Elmina Martha; Ria Hayuna (Fakultas Hukum Universitas Islam Indonesia, 2015)
This research discusses: first, the tendency of judges to impose imprisonment without considering any additional criminals in the form of counseling as a criminal sanction in KDRT (domestic violence); second, effective applicable policies in the implementation of Criminal Counseling. This research used normative approach with empirical data. The method of data collection was interview to judges to obtain primary data. The finding of this research shows: first, based on the existing facts, judges have never implemented any additional criminal in the form of counseling because it has not been well-known in court; there has not been any prosecution using Article 50 of UU PKDRT; the institution for counseling has not been established yet. Second, in the implementation of additional criminal counseling, efficient applicable policies in the future should refer to the idea of double track system, by optimizing both types of sanctions in a proportional manner (criminal sanctions and measures). Revision for stipulation in Article 50 point b is needed, so that it is more understandable and can soon be implemented by judges. In addition, the arrangement of standard operating procedure is needed for the implementation, supervision, and report of counseling process for the subject of domestic violence.